The Costs of Zombification in Europe: Why Austrian Economics Fails and the Empirical Findings for Japan are a Misleading Guide - Olaf Schlotmann; Frank Eberhardt (Credit and Capital Markets – Kredit und Kapital, 2020)
Supporters of the Austrian School of Economics and a number of empirical studies have claimed that the increasing number of "zombie" companies is a supply-side reason for the low growth rates in Europe. Often, these studies cite empirical findings for Japan to justify their claims, and conclude that in order to overcome the stagnation phase, bad investments and thus zombie companies should be eliminated from the production process. However, such creative destruction can only prove beneficial if innovative and highly productive companies replace these zombies under full utilization of resources. We ask whether findings on the zombie problem from empirical studies on Japan can be applied directly to the current European situation. We present facts contradicting the idea that productive companies would not have been able to exploit their growth potential in (southern) Europe, allegedly because they could not have found suitable employees since these were tied up in zombie companies on a massive scale. Even under the false assumption of full employment in Europe, existing empirical work shows that the losses due to zombification are only around 3.6?% of GDP over 10~years. In our calculation, that would be 100 euros per capita and year currently far too little to call for a drastic change in ECB monetary policy towards past long-run average short-term rates.
Keywords: B25; B53; D24; E22; E24; E32; E52; G23; J24; 330; Japan; Austrian School of Economics; Schumpeter; Creative Destruction; Monetary Policy; Costs of Zombification of Europe; Balance Sheet Recession; Secular Stagnation; Zombie Companies